The Effects of Group Work on Interaction and Learning Outcomes in Non Face-to-Face Synchronous General English Classes in the EFL Setting - Ji-Young, Seo (Journal of Education and e-Learning Research, 2021)
The effects of group work with assigned roles on learner-instructor interaction (LII), learner-learner interaction (LLI), and task achievement were investigated in non-face-to-face general English classes to determine implications for non-face-to-face online group work. The participants were 128 university students in South Korea. Zoom was employed for the synchronous classes (SC), and the university’s LMS (Learning Management System) was utilized for the asynchronous classes (AC). The participants were divided into three groups: Group A were assigned designated roles in SC, Group B were not assigned specific roles in SC, and Group C were assigned designated roles in AC. The students were required to produce two English presentation videos. The participants exchanged feedback and comments about the content and structure of the presentation script. The video production and editing through group work, a pre- and post-questionnaire, and task results were employed as analysis data. The results revealed that group work in which roles were assigned had a positive effect on LII and LLI. It should be noted that group work differs from face-to-face instruction. Thus, it is imperative that techers design detailed plans in advance and monitor student participation closely. Pedagogical implications and recommendations for future studies are outlined.